2010
DOI: 10.1375/ajgc.20.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills and Problem Behaviours of Children with Different Cognitive Styles Who Attend Preschool Education

Abstract: The study investigated whether social skills and problem behaviours of preschool children differ according to their cognitive styles. The sample group included 366 six-year-old children who attend preschools in Konya. Form A of the Kansas Reflection-Impulsivity Scale for Preschoolers (KRISP), developed by Wright (1971), was used to determine whether the participants had reflective or impulsive cognitive styles, while Preschool and Kindergarten Behaviour Scales (PKBS), developed by Merrell (2003), were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…But it is not easy to be identified, which makes a mixed curriculum entering kindergarten, which is really worrying. Literature [ 27 ] pointed out that the textbooks used in kindergartens in various places often coexist with multiple programs and focus on their own educational conditions, characteristics, or other specific circumstances. Some of these curriculum plans or teaching materials are created by relying on the professional strength of preschool education in colleges or kindergarten teachers.…”
Section: Related Workmentioning
confidence: 99%
“…But it is not easy to be identified, which makes a mixed curriculum entering kindergarten, which is really worrying. Literature [ 27 ] pointed out that the textbooks used in kindergartens in various places often coexist with multiple programs and focus on their own educational conditions, characteristics, or other specific circumstances. Some of these curriculum plans or teaching materials are created by relying on the professional strength of preschool education in colleges or kindergarten teachers.…”
Section: Related Workmentioning
confidence: 99%
“…In our concerted efforts to raise the educational level of children it is of primary importance that we take into account how we support this development, through informed, effective and cross-curricular practices (Roberts, 2005). A study of Seçer, Çeliköz, Koçyiğit, Seçer, & Kayılı (2010), to assess the relationship between social skills and behavior problems through PKBS Merrell (2002) and cognitive style and reflexivity-impulsivity by KRISP scale developed by Wright (1971), with 6-year-old children, attending Preschool Education showed that children with impulsive cognitive style show more behavior problems and children with cognitive style of reflexivity show more social skills. These studies show that impulsive children are less efficient than the reflective level of social skills, such as social cooperation, so cial interaction and social autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the importance of working on emotions and secondary social skills is evidenced by its impact on academic performance, the feeling of belonging to the educational community, optimal socialisation, and the wellbeing of students at this stage [27,71,72]. Therefore, it is appropriate to include and mobilise social skills, EI, and learning communities in the pedagogical designs of educational institutions of the 21st century.…”
Section: Learning Communities: a Commitment To Favouring The Feeling Of Belonging And Cultivating The Psychosocial Dimensions Of The Studmentioning
confidence: 99%